Development of AC-DC converter incorporating with active power filter for battery charger application: article / Mohd Hafiz Abdullah - Abdullah, Mohd Hafiz (Universiti Teknologi MARA (UiTM), 2014)
This paper present a smart AC-DC converter for battery charger application using boost rectification technique for power factor correction (PFC) to compensate the harmonics generated and to achieve a power factor near to unity. In this technique, the system used proportional-integral controller as a medium to reshape the current waveform to sinusoidal and in phase with the supply voltage waveform. The simulation of this circuit was done by using MATLAB Simulink software and hardware prototype was built according to this circuit design. The result shows that the current is operating in phase with the voltage, hence improve the power factor and reduces the THD level.